SURGICAL TREATMENT OF THE POST-TRAUMATIC PALPEBRAL PTOSIS - Claudia Florida Costea; D.Petraru (Romanian Society of Oral Rehabilitation, 2013)
We present the case of a 5 year old patient who comes to the II Clinic of Ophthalmology of "Prof. Nicolae Oblu" Clinical Emergency Hospital of Iaşi for correction of the right total unilateral palpebral ptosis Right Eye, 6 months after a palpebral trauma with a sharp object that sectioned a part of the orbicular muscle fibers and the levator muscle of the right upper lid. We mention that the surgical treatment performed was the correction of the palpebral ptosis, by shortening the upper lid levator muscle and reinsertion at its aponeurosis, considering the achievement of a functional and esthetic result. The reducing of the grade IV palpebral ptosis to grade II - I was aimed, letting free the visual axis.